﻿Determination of amino acids of plants from Angelica L. genus by HPLC method - Liliia Budniak; Liudmyla Slobodianiuk; Svitlana Marchyshyn; Ihor Potishnyi (Pensoft Publishers, 2022)
One of the tasks of pharmaceutical science is to find new sources of effective drugs. Such sources include plants such as Angelica archangelica L. and Angelica sylvestris L., which have been used for many years to treat various diseases in folk medicine. Because the chemical composition of these plants is poorly understood, the aim of our study was to investigate the amino acid composition of the leaves of A. archangelica L. and A. sylvestris L. The amino acids of the leaves of the study species of the genus Angelica L. were determined by the HPLC method. Eighteen free and nineteen bound amino acids were identified in the leaves of A. archangelica L. The A. sylvestris L. leaves contained nineteen free and the same amount of bound amino acids. High concentrations of free and bound amino acids such as L-glutamic acid and L-aspartic acid predominate in A. archangelica L. and A. sylvestris L. This allowed these amino acids to be considered distinguishing markers of the study plants. Character metabolic processes in which these amino acids take part may be associated with the medicinal properties of these plants pursuant to their use in medicine and, therefore, may contribute to the insight of their therapeutic properties.